Clinical and Genetic Characteristics, Management and Long-Term Follow-Up of Turkish Patients with Congenital Hyperinsulinism - Güven, Ayla (J Clin Res Pediatr Endocrinol, 2016)
OBJECTIVE: Mutations in the KATP channel genes is the most common cause of congenital hyperinsulinism (CHI) of infancy. Our aim was to report the clinical and genetic characteristics, treatment modalities, and long-term prognosis of patients with CHI. METHODS: Clinical and biochemical findings, operation procedures, and results of genetic analysis were retrospectively evaluated in 22 CHI patients from two pediatric endocrine centers in Turkey. RESULTS: Seven of the patients were born large for gestational age. Hypoglycemia was diagnosed within the first 24 hours of life in 9 patients and treatment with diazoxide (n=21) and/or somatostatin (n=8) had been attempted. Seven patients (31.8%) were unresponsive to medical treatment and underwent pancreatectomy. Histological examination of the pancreas confirmed diffuse disease in 6 patients. Diabetes developed in 3 patients following pancreatectomy (10 years, 2.5 years, and immediately after operation). The remaining four patients had neither recurrence of CHI nor of diabetes during the 3.67±0.7 years of follow-up. Sequence analysis identified mutations in 12 out of 19 patients (63%). Mutations in the ABCC8 gene were the most common finding and were found in 6 out of 7 patients who underwent pancreatectomy. Other mutations included a paternally inherited KCNJ11 mutation, a homozygous HADH mutation, and a heterozygous GLUD1 mutation. CONCLUSION: Mutations in the ABCC8 gene were the most common cause of CHI in our cohort. These mutations were identified in 85% of patients who underwent pancreatectomy. The development of diabetes mellitus after pancreatectomy may occur at any age and these patients should be screened regularly.